RELEVANSI PEMBATASAN PEMBUATAN AKTA NOTARIS TERHADAP KEDUDUKAN NOTARIS SEBAGAI PEJABAT UMUM - Laily Nur Azizah; Rusdianto Sesung (President University, 2016)
Supervision and guidance of Notaries is carried out by the Notary Supervisory Board on the implementation of Notary position duties based on the Notary Position Act and by the Notary Honorary Board for matters relating to the Notary Code of Ethics. With consideration to Article 4 point 16 of the Notary Code of Ethics concerning the prohibition for notaries to make deeds exceeding the fairness limit the amount of which has been determined by the next Honorary Board Notary issued the Honorary Board Regulation of the Indonesian Notary Association Number 1 of 2017 concerning Fairness Limits for the Making of the Deed stipulates that the fairness limit in making deeds is 20 (twenty) deeds per day.The author in this study wants to examine and analyze further about the position of the Honorary Board of the Central Indonesian Notary Association Regulation No. 1 2017 in the practice of notary and the relevance of the limitation on the number of notary deeds when associated with the notary's authority as a public official.The research method used is normative legal research, namely legal research carried out by examining library materials or secondary legal materials while the problem approach is carried out using a legal approach and conceptual approach.The results of the study indicate that the position of the Honorary Board Regulation of the Indonesian Notary Association Number 1 of 2017 in the practice of notary is only limited to regulations within the organization's internal scope and is not a statutory regulation that has binding nature. The limitation on the number of notary deeds is irrelevant because the function of the Notary is to serve the people who need their services and Notaries are not permitted by the Act of Notary Position to reject the parties who come to make the deed.